Effect of Glutaraldehyde Crosslinking Parameters on Mechanical and Wetting Properties of PVA/NaAlg Electrospun Mat - Ayben Pakolpakçıl (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Electrospun alginate-based materials are used in a wide range of applications, including wound dressings, tissue engineering, batteries, water treatment, bioremediation, and food packaging. However, they have low resistance to water. Crosslinking is usually used to enhance the mechanical properties of water-soluble polymers. Process parameters also play a key role in the crosslinking process. In this study, materials from sodium alginate (NaAlg) and poly (vinyl alcohol) (PVA) were prepared using the electrospinning method. To investigate the effect of the process parameters on the mechanical properties of the materials, different concentrations (1.25, 2.5 and 5 v %) and different application times (10 min, 60 min and 24 h) of the crosslinking agent were used. The wettability and mechanical properties of the electrospun mats were evaluated using a water contact angle device and a tensile strength tester, respectively. The maximum tensile strength was measured at 7 MPa which is the sample treated at 5% glutaraldehyde (GA) concentration and 60 min of application time. The sample treated with 2.5% GA concentration and 60 min of treatment time had the highest measured elongation of 11.5%. The sample treated with 2.5% GA concentration and for 10 min had the lowest water contact angle, which was measured at 27.5°. The intended usage of the materials should be considered, as the concentration of the crosslinking process and duration might affect the water-soluble polymers' mechanical and wetting properties.